Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

Expériences de soins à domicile et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de synthèse décrit les principaux constats de l'étude, accompagnés de quelques citations de participants.

Expériences de soins à domicile et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de recherche intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Home Care Experiences and Language Challenges in Ontario: Perspectives of Francophone Seniors, Family Caregivers, Frontline Care Providers, and Managers. Summary report - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de synthèse décrit les principaux constats de l'étude, accompagnés de quelques citations de participants.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.